Optimalisasi Penerimaan Pendapatan Asli Daerah Sektor Pajak Bumi dan Bangunan Perdesaan dan Perkotaan - Nugrahadi, Robi (Jurnal Ilmiah Administrasi Publik, 2018)
Since The Law of Local Tax Number 28 in 2009 apply, Property Tax become one of the local tax that is manage by local government. Existence opportunity of property tax require the local government to optimize program in order to use budget efficiently and increase local revenue. Optimum program is the best effort to increase local revenue. This research intent on make an analysis the factors which must be prepare and the strategy that is planned to increase local revenue. This research approach is qualitative with literature study method. The results indicate that any factors which must be prepare efficiently to manage property tax, that is implementation regulation, human resources, infrastructure tool, and exist budget. Be sides the factor, strategy which must be done to increase local revenue, that is mapping sell value of the land object, update tax data object, giving primeservice, collecting with structure, and giving information on whole a scale.